What is the Effectiveness of the Financial Information Processing Cell in Combating Money Laundering Crime in Light of the Information Systems? - Zerouak, Aicha (Journal of Legal Studies and Researches, 2023)
This study aims to highlight the role of the FIPC in combating money laundering within the framework of the policy of the Algerian legislator by providing suitable legislative and regulatory frames to combat this crime. However, the development of the information systems and the criminal methods used in money laundering made it even more dangerous and harder for the cell to combat it.